Effect of Different Systems Of Grazin6 By Cattle On Lasiurus-Eleusine-Aristida Grassland In Arid Region Of Rajasthan Vis-A-Vis Animal Production - Prajapati, M C (Annals of Arid Zone, 2016)
An experiment with four main treatments (seven sub-treatments) of grazing systems for cattle to obtain optimum animal production consistent with sustained range resources was carried out in a replicated randomised manner with five replications on a 'Good' condition class Lasirus-EleuBine-Aristida type rangeland at the Range Management and Soil Conservation Paddock, Jaisalmer from 1965 to 1968. Continuous grazing ( TI ), deferred grazing with fixed number of animals on an unit area in half of the grazing period i. e., two months alternate grazing (T2P, and 12P2) without any specific provision for seed production two months (12P2 and T4PI) or four months (T3P2) early grazings are detrimental to the range vegetation as compared to early deferment of grazing during growing (August-September) and spring (March-April) seasons (T4P2). It is more beneficial when the period of early deferment is of four months viz., August to November (T3P.) as it allows the forage plant community to complete the life cycle and produce sufficient seed for future regeneration. Moreover the reproduction from vegetative organs is not disturbed and the desirable species complete well to keep down the less desirable ones. In this treatment of T3PI, as regards the plant behaviour, the de creasers were minimum and invaders and unaffected ones were maximum. The invading disappearing ratio (lID Ratio) was highest. Although the animal production was significantly higher under continuous grazing (T.), it was steady, consistent and less fluctuating only in the next best treatment of T3. Slow and steady gains in animal production are more desirable than fluctuating higher gains.